2020
DOI: 10.4014/jmb.2001.01052
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Microbial Cell Factory for the Extracellular Production of Catalytically Active Phospholipase A2 of Streptomyces violaceoruber

Abstract: Phospholipase A 2 (PLA 2 ) from Streptomyces violaceoruber is a lipolytic enzyme used in a wide range of industrial applications including production of lysolecithins and enzymatic degumming of edible oils. We have therefore investigated expression and secretion of PLA 2 in two workhorse microbes, Pichia pastoris and Escherichia coli . The PLA 2 was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…2 C). The results of this study and earlier studies (Jung & Park, 2008 ; Lee et al, 2020 ) suggested that more rapid expression of target proteins via supplementation of rare-codon tRNAs may lead to a higher accumulation of target proteins, which in turn accelerates misfolding and/or degradation of the proteins. We noted that the values of specific activities associated with CMC were much lower than those associated with Avicel, which is consistent with a previous study which reported that the main catalytic activity of CelA was attributed to the GH9 module, a major characteristic of which is endoglucanase activity (Yi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 66%
“…2 C). The results of this study and earlier studies (Jung & Park, 2008 ; Lee et al, 2020 ) suggested that more rapid expression of target proteins via supplementation of rare-codon tRNAs may lead to a higher accumulation of target proteins, which in turn accelerates misfolding and/or degradation of the proteins. We noted that the values of specific activities associated with CMC were much lower than those associated with Avicel, which is consistent with a previous study which reported that the main catalytic activity of CelA was attributed to the GH9 module, a major characteristic of which is endoglucanase activity (Yi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 66%
“…We previously observed that engineered E. coli BL21 star (DE3) strains expressing PLA 2 from S. violaceoruber [ 23 ] or a truncational mutant (TM1) of CelA from Caldicellulosiruptor bescii [ 20 ] with the aid of signal peptides could secrete endogenous proteins into the culture medium in a non‐specific manner. This observation suggests that PLA 2 with the N‐terminal PelB signal peptide (P‐PLA 2 ) and TM1 with the N‐terminal DsbA signal peptide (D‐TM1) could serve as co‐expression partners that help FKP and FucT2 to be secreted into the culture medium (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] Therefore, instead of searching for a signal peptide suitable for the secretion of FKP and FucT2, we decided to exploit heterologous proteins capable of inducing non‐specific secretion of cytoplasmic proteins into the culture medium. We previously observed the non‐specific secretion of numerous endogenous proteins into the culture medium when P‐PLA 2 [ 23 ] and D‐TM1 [ 20 ] were expressed in E. coli . Therefore, these two heterologous proteins were selected as co‐expression partners to mediate the extracellular secretion of FKP and FucT2.…”
Section: Discussionmentioning
confidence: 99%
“…DCW). E. coli BL21 Star (DE3) is characterized by containing a mutated rne131 gene encoding ribonuclease E (RNaseE), which can enhance the stability of messenger RNA, which in turn elevates the expression level of target proteins ( Lee et al, 2020 ). Hence, the E. coli BL21 Star (DE3) carrying the plasmid pMM was used as a chassis and cultivated in SBMSN medium to evaluate the yield of GA.…”
Section: Resultsmentioning
confidence: 99%